Cardiopulmonary interactions—which monitoring tools to use? - Berger, David; Werner Moller, Per; Bachmann, Kaspar F. (Frontiers in Physiology, 2023)
Heart-lung interactions occur due to the mechanical influence of intrathoracic pressure and lung volume changes on cardiac and circulatory function. These interactions manifest as respiratory fluctuations in venous, pulmonary, and arterial pressures, potentially affecting stroke volume. In the context of functional hemodynamic monitoring, pulse or stroke volume variation (PPV or SVV) are commonly employed to assess volume or preload responsiveness.However, correct interpretation of these parameters requires a comprehensive understanding of the physiological factors that determine pulse pressure and stroke volume.These factors include pleural pressure, venous return, pulmonary vessel function, lung mechanics, gas exchange, and specific cardiac factors. A comprehensive knowledge of heartlung physiology is vital to avoid clinical misjudgments, particularly in cases of right ventricular (RV) failure or diastolic dysfunction. Therefore, when selecting monitoring devices or technologies, these considerations must be considered.Invasive arterial pressure measurements of variations in breath-to-breath pressure swings are commonly used to monitor heart-lung interactions. Echocardiography or pulmonary artery catheters are valuable tools for differentiating preload responsiveness from RV failure, while changes in diastolic function should be assessed alongside alterations in airway or pleural pressure, which can be approximated by esophageal pressure. In complex clinical scenarios like ARDS, combined forms of shock or right heart failure, additional information on gas exchange and pulmonary mechanics aids in the interpretation of heart-lung interactions. This review aims to describe monitoring techniques that provide clinicians with an integrative understanding of a patient's condition, enabling accurate assessment and patient care.